A composite solid-state electrolyte for a substation battery and a method of making the same
Patent Information
- Application Number
- CN202611367027.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-30
AI Technical Summary
但该方案应用于变电站蓄电池时,仍面临以下问题:气凝胶压制时极易开裂,成膜率低;LLZTO和LATP表面易形成Li2CO3钝化层,LATP在水系环境中缺乏水相暴露时间控制,离子电导率易衰减;辅助填料与聚合物基体缺乏化学键合,长期循环界面易剥离;自然晾干方式溶剂挥发不可控,易致膜体开裂且引入杂质
本发明提供了一种用于变电站蓄电池的复合固态电解质及其制备方法,通过构建三维连续多孔无机骨架与聚合物电解质的互穿网络结构,实现了高离子电导率、优异机械强度与良好界面稳定性的协同提升。其核心发明构思在于:首先,选用LLZTO和/或LATP作为高离子电导率的无机骨架主体,并引入经表面改性的一维或二维电子绝缘性辅助填料,二者协同构建出孔隙率为30-60%、厚度为30-120μm且具有优异机械韧性的三维连续多孔骨架。该骨架不仅为锂离子提供了高速传输通道,有效规避了聚合物电解质室温电导率低的缺陷,而且一维/二维填料形成的物理网络能显著抑制锂枝晶的纵向穿刺,大幅提升电池安全性。其次,通过将聚合物电解质(PEO和/或PVDF-HFP基)充分填充于上述多孔骨架中,利用无机骨架的刚性支撑作用,克服了纯聚合物电解质机械强度差、易蠕变的不足,同时聚合物相有效改善了无机颗粒间的界面接触,降低了晶界电阻。这种复合设计,使得电解质在保持高离子迁移数的同时,具备了适应变电站蓄电池宽温域运行和长循环寿命需求的综合性能。
Smart Images

Figure CN123018098A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid electrolyte technology, and more specifically to a composite solid electrolyte for substation batteries and its preparation method. Background Technology
[0002] DC power supply systems in substations are critical equipment for ensuring the safe and stable operation of power systems. Currently, valve-regulated lead-acid batteries are commonly used in substation DC power supply systems. However, lead-acid batteries suffer from prominent problems such as low energy density, short cycle life, and high risk of thermal runaway under high-temperature float charging. Lithium iron phosphate-based solid-state batteries are considered an ideal alternative to substation energy storage batteries due to their high safety and long cycle life. The core of solid-state batteries is the solid electrolyte, whose performance directly affects the battery's ion conduction, thermal stability, and interfacial stability. Currently, inorganic solid electrolytes (such as LLZTO and LATP) have good thermal stability and a wide electrochemical window, but poor machinability and high brittleness; polymer solid electrolytes (such as PEO) are easy to process, but have low ionic conductivity at room temperature and are prone to softening at high temperatures. The long-term float charging and wide temperature range operation of substation batteries place stringent requirements on the comprehensive performance of the electrolyte.
[0003] Therefore, composite solid electrolytes containing polymers and inorganic fillers have become an important technological approach. Chinese patent application CN202210955308.6 discloses a composite solid electrolyte and its preparation method: inorganic electrolytes and auxiliary fillers are dispersed in water, freeze-dried to obtain inorganic aerogel, pressed into a membrane, impregnated with a polymer electrolyte solution, and dried to obtain a composite solid electrolyte. However, when this method is applied to substation batteries, it still faces the following problems: aerogels are prone to cracking during pressing, resulting in low film formation rate; Li2CO3 passivation layers easily form on the surfaces of LLZTO and LATP, and LATP lacks control over aqueous phase exposure time in aqueous environments, leading to easy decay of ionic conductivity; auxiliary fillers lack chemical bonding with the polymer matrix, and the interface is prone to peeling during long-term cycling; solvent evaporation is uncontrollable in natural drying methods, easily causing membrane cracking and introducing impurities.
[0004] To address the aforementioned shortcomings, this invention continues the composite structure concept of "inorganic aerogel framework + polymer electrolyte filler." A three-dimensional porous framework is constructed through freeze-drying, and the pores are filled with polymer electrolyte to form a composite solid electrolyte that combines high ionic conductivity and good processability. Furthermore, the passivation layer is removed by dry annealing or rapid treatment with extremely dilute organic acids; the auxiliary filler is surface activated and silanized to enhance interfacial chemical bonding; vacuum-atmospheric pressure cyclic impregnation is used to improve the filling rate; and step-by-step desolventizing drying under an inert atmosphere avoids contamination and cracking.
[0005] Therefore, there is an urgent need to develop a composite solid electrolyte specifically for substation batteries, aiming to meet the comprehensive requirements of this application scenario for high ionic conductivity, long cycle life and high safety. Summary of the Invention
[0006] To address the problems of the prior art, this invention provides a composite solid electrolyte for substation batteries and its preparation method. The composite solid electrolyte has advantages such as high ionic conductivity, long cycle life, and high safety, and can meet the application requirements of substation batteries.
[0007] The technical solution of the present invention to solve the above problems is as follows: A composite solid electrolyte for substation batteries includes a porous inorganic framework and a polymer electrolyte filling the pores of the porous inorganic framework. The porous inorganic framework is composed of an inorganic solid electrolyte and a surface-modified electronic insulating auxiliary filler. The inorganic solid electrolyte in the porous inorganic framework has a mass percentage of 70-95 wt%. The inorganic solid electrolyte is LLZTO and / or LATP. The electronic insulating auxiliary filler is an electronic insulating material with a one-dimensional or two-dimensional morphology. The porous inorganic framework has a three-dimensional continuous porous structure formed by freeze drying. The porous inorganic framework has a porosity of 30-60% and a thickness of 30-120 μm before being filled with the polymer electrolyte. The polymer electrolyte comprises a lithium salt and a polymer matrix, wherein the lithium salt is LiTFSI and / or LiFSI, and the polymer matrix is PEO and / or PVDF-HFP; In the composite solid electrolyte, the porous inorganic framework has a mass percentage of 40-80 wt%, and the remainder is a polymer electrolyte.
[0008] The composite solid electrolyte is a composite structure consisting of a porous inorganic framework and a polymer electrolyte filling its pores, providing a continuous transport channel for lithium ions. The porous framework is formed by the inorganic solid electrolyte and surface-modified electronically insulating auxiliary fillers. The auxiliary fillers, after surface modification, form chemical bonds with the polymer matrix, enhancing interfacial adhesion. The auxiliary fillers are one-dimensional or two-dimensional electronically insulating materials. Their one-dimensional / two-dimensional morphology allows them to interconnect to form a three-dimensional network structure, enhancing the mechanical strength and toughness of the framework. The electronic insulation effectively suppresses the risk of internal short circuits after the formation of the three-dimensional conductive network. The porous inorganic framework has a three-dimensional continuous porous structure formed by freeze-drying. This structure is naturally formed by the sublimation of ice crystals during freeze-drying, exhibiting high porosity and interconnected pores, providing ample space and a continuous ion transport path for the polymer electrolyte. The polymer electrolyte contains lithium salt and a PEO and / or PVDF-HFP matrix. The lithium salt provides the lithium ion source, and the polymer matrix provides ion conduction channels at room temperature and acts as a flexible filler material to fill the framework pores, forming a continuous ion-conducting phase.
[0009] Furthermore, the electronic insulating auxiliary filler is selected from one or more of boron nitride nanosheets, alumina nanofibers, silica nanofibers, boehmite nanosheets, and aluminum nitride nanosheets; the surface-modified electronic insulating auxiliary filler is an auxiliary filler that has undergone surface activation and silanization modification.
[0010] After surface activation and silanization modification, the auxiliary filler is grafted with organic functional groups, which can form chemical bonds when it is compounded with polymer electrolyte, thereby enhancing the interfacial bonding force between the filler and the polymer matrix and avoiding performance degradation caused by physical adsorption and interfacial peeling during long-term cycling.
[0011] Furthermore, in the polymer electrolyte, the polymer matrix is a blend of PEO and PVDF-HFP, wherein the EO / Li molar ratio is 8-20:1, and the polymer electrolyte fills at least 85% of the pores of the porous inorganic framework.
[0012] A method for preparing a composite solid electrolyte for substation batteries includes the following steps: S1: The inorganic solid electrolyte powder is subjected to surface purification pretreatment under an inert atmosphere to obtain pretreated inorganic solid electrolyte powder. S1 surface cleaning pretreatment is used to remove the Li2CO3 / LiOH lithium-repellent passivation layer formed on the surface of inorganic solid electrolyte powder (LLZTO and / or LATP) due to long-term exposure to air. This passivation layer will seriously deteriorate the interfacial contact between the electrolyte and the electrode, resulting in a sharp increase in interfacial impedance. Pretreatment can significantly reduce interfacial impedance and restore the intrinsic ion transport performance and interfacial wettability of the electrolyte. S2: Modified auxiliary filler is obtained by surface activation and silanization modification of electronic insulating auxiliary filler; S2 surface activation and silanization modification are used to introduce active functional groups on the surface of electronic insulating auxiliary fillers, transforming the filler from an inert surface into an active surface that can participate in chemical bonding. After silanization modification, the organic functional groups grafted on the filler surface can form chemical bonds with the polymer matrix in subsequent steps, enhancing the interfacial bonding force between the filler and the polymer and preventing the physical adsorption interface from peeling off during long-term cycling. S3: The pretreated inorganic solid electrolyte powder obtained in step S1 and the modified auxiliary filler obtained in step S2 are dispersed in degassed deionized water to form a suspension under a dry atmosphere with a dew point ≤ -40℃. The suspension is coated and then pre-frozen and freeze-dried to obtain a porous inorganic tape. The porous inorganic tape is then subjected to multi-stage gradient rolling to obtain a porous inorganic skeleton membrane. S3 disperses pretreated inorganic powder and modified auxiliary fillers in degassed deionized water under a low dew point dry atmosphere to form a suspension. The low dew point atmosphere prevents moisture and CO2 in the air from reacting with the oxide electrolyte surface to regenerate the passivation layer. The degassed deionized water reduces the erosion of LATP by dissolved oxygen and CO2. After coating, pre-freezing allows the water in the suspension to quickly crystallize into fine and uniform ice crystals. The ice crystals sublimate during subsequent freeze-drying, leaving a three-dimensional interconnected porous structure. Freeze-drying at low temperature and low pressure allows the ice crystals to sublimate directly, avoiding the damage to the porous structure caused by the surface tension of liquid water and preserving the three-dimensional porous framework. S4: Dissolve the polymer matrix and lithium salt in an organic solvent to prepare a polymer electrolyte impregnation solution; S5: The porous inorganic framework membrane obtained in step S3 is vacuum impregnated with the polymer electrolyte impregnation solution obtained in step S4, and then dried by step-by-step solvent removal under an inert atmosphere to obtain a composite solid electrolyte. S5 vacuum impregnation removes gas from the pores by vacuuming, and after the impregnation liquid is injected, the liquid fully fills the pores under the drive of capillary force and pressure; step-by-step solvent removal drying removes the solvent step by step by increasing the temperature, avoiding the shrinkage and cracking of the membrane caused by rapid evaporation of the solvent, and the inert atmosphere avoids polymer oxidation and moisture introduction at high temperature. S6: The composite solid electrolyte obtained in step S5 is heat-treated in an inert atmosphere and cooled to obtain a composite solid electrolyte for substation batteries.
[0013] Further, the surface cleaning pretreatment in step S1 is either dry annealing or wet cleaning. The dry annealing includes annealing the inorganic solid electrolyte powder in a continuously flowing inert atmosphere at 550-750℃ and a dew point ≤-40℃ for 1-4 hours, and then cooling it to no higher than 80℃ in an inert atmosphere after annealing. The wet purification process includes: treating the inorganic solid electrolyte powder in a 0.005-0.05M citric acid and / or acetic acid solution at 20-30℃ for 1-5 minutes, washing it, rinsing it with a 0.005-0.02M LiOH solution for 10-60 seconds, filtering it under vacuum and washing it with deionized water until the filtrate is neutral, and then vacuum drying it at 80-120℃.
[0014] Dry annealing is carried out at high temperature (550-750℃) under a continuously flowing inert atmosphere with a dew point ≤-40℃. The continuously flowing inert atmosphere removes CO2 and water vapor, disrupting the chemical equilibrium and causing the thin Li2CO3 passivation layer on the surface of LLZTO powder to decompose or be consumed by a solid-phase reaction. The generated CO2 escapes with the airflow, while the surface LiOH impurities are removed by heat, thus removing the passivation layer. The dew point ≤-40℃ avoids the reaction between moisture in the air and the oxide surface during the annealing process.
[0015] The wet purification process employs a low-concentration organic acid for rapid treatment at room temperature. The organic acid selectively dissolves the surface Li₂CO₃ / LiOH passivation layer, and the low concentration and short treatment time minimize corrosion to the electrolyte matrix. Subsequently, the solution is rinsed with LiOH for 10-60 seconds to compensate for any H₂ that may have been released during the acid treatment. + / Li + The exchange-induced loss of surface lithium suppresses surface lithium deficiency; this step is particularly suitable for LATP because LATP exhibits lithium degradation in aqueous environments. + Dissolution can lead to crystal structure damage and decreased ionic conductivity; vacuum drying at 80-120℃ ensures that the powder moisture content is ≤500ppm, avoiding side reactions caused by residual moisture in subsequent processes. Both methods can achieve the purpose of removing the surface passivation layer and reducing interfacial impedance; the appropriate solution can be selected according to the actual production conditions.
[0016] Further, the surface activation in step S2 is performed by oxygen plasma treatment at a power of 100-500W and a pressure of 10-100Pa for 1-10 minutes; the silanization modification includes: dispersing the surface-activated electronic insulating auxiliary filler in an ethanol / water mixed solvent, adding one or more of KH550, KH560, and KH570 as silane coupling agents, and reacting at 40-70℃ for 1-4 hours.
[0017] Oxygen plasma treatment is performed at 100-500W power and 10-100Pa pressure for 1-10 minutes. High-energy plasma bombards the surface of the auxiliary filler, introducing active oxygen-containing functional groups such as hydroxyl and carboxyl groups, while simultaneously cleaning surface impurities, providing a chemical anchor for the subsequent silanization reaction. This treatment method is dry and solvent-free, with short processing time and uniform effect. Silanization modification is carried out in an ethanol / water mixed solvent. Silane coupling agents such as KH550, KH560, and KH570 contain hydrolyzable alkoxy groups (-OR) and organic functional groups (amino, epoxy, vinyl, etc.). After hydrolysis, the alkoxy groups condense with the hydroxyl groups on the activated filler surface to form Si-OM chemical bonds, grafting organic functional groups onto the filler surface. The introduction of organic functional groups transforms the filler surface from a hydrophilic surface to an active surface that can participate in the polymerization reaction. During subsequent composite with the polymer matrix, chemical bonding can be formed instead of relying solely on physical adsorption, significantly enhancing interfacial adhesion and long-term cycling stability.
[0018] Furthermore, in step S3, the solid content of the suspension is 35-60 wt%, and the time from adding degassed deionized water to completing the pre-freezing molding does not exceed 120 min. When the inorganic solid electrolyte is LLZTO, the pH of the suspension is 10.0-11.5; when the inorganic solid electrolyte is LATP, the pH of the suspension is 7.0-8.5; when the inorganic solid electrolyte is a mixture of LLZTO and LATP, the pH of the suspension is 8.5-10.0. The suspension also contains a forming aid, which is selected from one or more of PVP, PVA, CMC, sodium alginate, and PEO. The amount of the forming aid added is 0.2-1.5 wt% of the total mass of the pretreated inorganic solid electrolyte powder obtained in step S1 and the modified auxiliary filler obtained in step S2.
[0019] The time from powder immersion in water to completion of pre-freezing should not exceed 120 minutes. Strict control of the aqueous phase exposure time is crucial because LATP gradually undergoes Ti oxidation in an aqueous environment. 4+ Reduction and hydrolysis of phosphate groups lead to irreversible decay of ionic conductivity. This time-limited control reduces the degradation of LATP. Different electrolytes are controlled by graded pH. LLZTO is stable in an alkaline environment (pH=10.0-11.5), while LATP is stable in a slightly alkaline environment (pH=7.0-8.5). The mixed system uses the middle value (pH=8.5-10.0). Graded control ensures that each electrolyte is dispersed in the water within its stable pH range.
[0020] Further, in step S3, the coating thickness is 0.3-1.5 mm, the pre-freezing temperature is -60℃ to -30℃, and the belt speed is 0.1-0.5 m / min; the freeze-drying is: drying once at -35℃ to -20℃ and 1-10 Pa for 6-14 h, and then drying a second time at 20-40℃ for 2-6 h; The pre-frozen strips are stacked in 2-3 layers on a freeze-drying tray, with a breathable isolation membrane between adjacent strips. From top to bottom, the pore size and / or porosity of the breathable isolation membrane increases layer by layer. The multi-stage gradient rolling process consists of 2-5 stages, with a single-stage reduction rate of ≤20%. The rollers are preheated at 40-70℃ for 5-20 minutes before rolling.
[0021] The freeze-drying process employs a two-stage method: The first stage involves drying at -35°C to -20°C and 1-10 Pa for 6-14 hours, allowing ice crystals to sublimate directly below their triple point, removing most of the moisture. The temperature and pressure conditions at this stage ensure that the ice crystals are removed through sublimation rather than melting, preserving the three-dimensional porous structure. The second stage involves drying at 20-40°C for 2-6 hours, removing bound water and residual moisture, reducing the moisture content of the skeleton to below 1000 ppm. The strips are stacked in 2-3 layers on a tray to ensure uniform drying. To increase batch production capacity, a breathable isolation membrane is set between layers to prevent interlayer adhesion. The pore size / porosity increases layer by layer from top to bottom. The bottom strip is closest to the heating shelf, has the highest heat input and the longest water vapor escape path, so it needs a more breathable isolation membrane to enhance mass transfer, remove excess heat and prevent ice crystals from melting due to overheating. The top strip is the opposite. This gradient design makes the drying rate of each layer of strip tend to be consistent. Multi-level gradient rolling is applied at 2-5 levels with a single-level reduction rate of ≤20%. Gradual pressure is applied to avoid cracking caused by large deformation at one time.
[0022] Further, in step S4, the solid content of the polymer electrolyte impregnation solution is 3-15wt%, the viscosity at 25℃ is 10-500mPa·s, and the moisture content is not higher than 200ppm; in step S5, the vacuum impregnation is a vacuum-atmospheric pressure cyclic impregnation, cyclically repeated 2-5 times; the step-by-step desolventizing includes three stages: surface desolventizing at 20-25℃ under atmospheric pressure inert atmosphere for 15-20min, low-temperature vacuum drying at 35-45℃ and ≤1000Pa for 2-4h, and deep vacuum drying at 50-55℃ and ≤100Pa for 4-6h.
[0023] Vacuum-atmospheric pressure cyclic impregnation drives the impregnating liquid to repeatedly enter and exit the pores through 2-5 pressure alternations, effectively removing residual gas from the pores and significantly improving the pore filling rate. Stepped solvent removal employs a three-stage gradient heating: the first stage is surface solvent removal at 20-35℃ under an atmospheric pressure inert atmosphere, gently removing most of the surface solvent and avoiding membrane shrinkage and cracking caused by rapid evaporation; the second stage is low-temperature vacuum drying at 35-50℃ and ≤1000Pa, further removing solvent from the pores under reduced pressure; the third stage is deep vacuum drying at 50-70℃ and ≤100Pa, reducing residual solvent to extremely low levels under high vacuum and moderate heating. The three stages are progressively advanced to ensure complete solvent removal at a safe and controllable rate, while the inert atmosphere throughout the process prevents polymer oxidation.
[0024] Furthermore, the heat treatment temperature in step S6 is 50-80℃, the time is 1-4h, and after heat treatment, it is slowly cooled at a rate of 0.5-5℃ / min.
[0025] The present invention has the following beneficial effects: This invention provides a composite solid electrolyte for substation batteries and its preparation method. By constructing an interpenetrating network structure of a three-dimensional continuous porous inorganic framework and a polymer electrolyte, a synergistic improvement in high ionic conductivity, excellent mechanical strength, and good interfacial stability is achieved. The core inventive concept lies in: firstly, using LLZTO and / or LATP as the main body of the high ionic conductivity inorganic framework, and introducing surface-modified one-dimensional or two-dimensional electronic insulating auxiliary fillers. These two components synergistically construct a three-dimensional continuous porous framework with a porosity of 30-60%, a thickness of 30-120 μm, and excellent mechanical toughness. This framework not only provides a high-speed transport channel for lithium ions, effectively avoiding the low room-temperature conductivity of polymer electrolytes, but also the physical network formed by the one-dimensional / two-dimensional fillers significantly suppresses the longitudinal penetration of lithium dendrites, greatly improving battery safety. Secondly, by fully filling the aforementioned porous framework with polymer electrolytes (PEO and / or PVDF-HFP based), the rigid support of the inorganic framework overcomes the shortcomings of pure polymer electrolytes, such as poor mechanical strength and easy creep. Simultaneously, the polymer phase effectively improves the interfacial contact between inorganic particles and reduces grain boundary resistance. This composite design enables the electrolyte to maintain a high ion transport number while possessing comprehensive performance characteristics suitable for the wide temperature range operation and long cycle life requirements of substation batteries.
[0026] Furthermore, this invention solves key common problems in the preparation of composite solid electrolytes through a series of progressive process optimizations. In the raw material pretreatment stage, addressing the issues of LLZTO / LATP's hygroscopic deterioration and the agglomeration of auxiliary fillers, dry annealing / wet purification under an inert atmosphere and surface activation / silanization modification techniques were employed. These techniques removed surface impurities at the source and introduced active functional groups, significantly enhancing the interfacial compatibility and bonding force between the inorganic and polymer phases. In the framework forming stage, the suspension was prepared under a dry atmosphere with a dew point ≤ -40℃, the exposure time of the aqueous phase was strictly controlled, and a differentiated pH control strategy was combined to effectively suppress the hydrolysis side reactions of the inorganic solid electrolyte in an aqueous environment. Combined with a multi-stage gradient rolling process, the uniformity of the framework film thickness was ensured while preserving the pore structure. In the composite stage, a vacuum-atmospheric pressure cyclic impregnation combined with a step-by-step solvent removal and drying technique was used to ensure a high filling rate (≥85%) of the polymer electrolyte in the porous framework pores and to avoid solvent residue, thus preventing surface crusting and internal pore defects caused by traditional drying methods. Finally, the post-heat treatment process further promoted the rearrangement and crystallization regulation of polymer segments on the inorganic framework surface, optimizing the interfacial lithium-ion transport kinetics. These improvements, based on the core inventive concept, enable the composite solid electrolyte of this invention to better adapt to the operating characteristics of substation batteries, including long-term float charging, deep cycling, and wide temperature range operation, significantly improving battery safety, cycle life, and environmental adaptability. Attached Figure Description
[0027] Figure 1 The ionic conductivity test results are for the examples and comparative examples; Figure 2 The results show the interface impedance test results for the examples and comparative examples. Detailed Implementation
[0028] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0029] All raw materials used in the following examples are commercially available products. LLZTO powder D50=300nm; LATP powder D50=500nm; boron nitride nanosheets thickness <5nm, sheet diameter 0.5-2μm; alumina nanofibers diameter approximately 50nm, aspect ratio >50; silica nanofibers diameter approximately 30nm, aspect ratio >80; boehmite nanosheets sheet diameter 100-300nm; PEO number-average molecular weight 4×10⁻⁶. 5 -6×105 g / mol; HFP content in PVDF-HFP is 8-20wt%; LiTFSI and LiFSI purity is ≥99.9%, and moisture content is ≤100ppm.
[0030] Example 1 A method for preparing a composite solid electrolyte for substation batteries, specifically comprising: Step S1: LLZTO surface cleaning pretreatment (dry annealing) LLZTO powder was placed in a tube furnace and annealed at 650°C at a rate of 5°C / min under a continuously flowing Ar atmosphere with a dew point ≤ -40°C, and held for 3 hours. After annealing, the powder was naturally cooled to no higher than 80°C under an Ar atmosphere to obtain pretreated LLZTO powder, which was then transferred to a sealed container for later use.
[0031] Step S2: Surface activation and silanization modification of boron nitride nanosheets Boron nitride nanosheets were placed in a plasma treatment chamber and activated with oxygen plasma for 5 min at a power of 300 W and a pressure of 50 Pa. The activated boron nitride nanosheets were then dispersed in an ethanol / water mixed solvent (volume ratio 90:10) at a ratio of 1 g:20 mL. 2 wt% (by weight of boron nitride nanosheets) of KH550 silane coupling agent was added, and the pH was adjusted to 5.0 with 0.1 mol / L acetic acid solution. The reaction was stirred at 60 °C for 2 h. After the reaction, the nanosheets were centrifuged, washed three times with ethanol, and dried under vacuum at 80 °C for 6 h to obtain the modified boron nitride nanosheets.
[0032] Step S3: Water-based freeze forming In an Ar atmosphere glove box with a dew point ≤ -40℃, 80g of pretreated LLZTO powder obtained in step S1, 20g of modified boron nitride nanosheets obtained in step S2, and 1.0g of PVP forming aid (1.0wt% of the total inorganic solid mass) were mixed. The above solid materials were added to 200mL of degassed deionized water (inorganic electrolyte:water = 1:2.5), and the pH of the suspension was adjusted to 10.5 with 0.1 mol / L LiOH solution. The mixture was stirred at 15℃ for 20 min, ultrasonically dispersed for 10 min, and then vacuum degassed for 10 min to obtain the suspension. The total aqueous phase exposure time from powder immersion in water to completion of coating was 50 min.
[0033] The suspension was uniformly coated onto a stainless steel conveyor belt using a slit coating method, with a coating thickness of 1.0 mm and a belt speed of 0.3 m / min. The belt was then frozen in a -45℃ pre-freezing zone for approximately 12 minutes. The frozen belt was automatically cut to 30 cm × 40 cm dimensions and stacked in three layers on a freeze-drying tray. A PTFE microporous breathable membrane was placed between the layers, with pore sizes of 0.3 μm, 1.0 μm, and 3.0 μm from top to bottom, and porosities of 65%, 75%, and 85%, respectively.
[0034] The trays were fed into a batch freeze dryer and dried for 10 hours at -30°C and 5 Pa, followed by a second drying at 30°C for 4 hours. After freeze-drying, the aerogel tape was preheated at 60°C for 10 minutes and then subjected to a three-stage gradient rolling process: the first stage had a roll gap of 0.45 mm / pressure of 8 MPa, the second stage had a roll gap of 0.30 mm / pressure of 10 MPa, and the final stage had a roll gap of 0.15 mm / pressure of 12 MPa. The single-stage reduction rate was approximately 25%, resulting in a porous inorganic framework membrane with a thickness of approximately 150 μm. The membrane was then wound up for later use, and the framework porosity was 45%.
[0035] Step S4: Preparation of polymer electrolyte impregnation solution PEO and PVDF-HFP were blended at a mass ratio of 60:40 to obtain a polymer blend. 30 g of the polymer blend was dissolved in 600 mL of tetrahydrofuran and refluxed at 55 °C for 3 h. Approximately 3.6 g of LiTFSI was added at an EO / Li molar ratio of 12:1, and stirring continued for 1 h to obtain a polymer electrolyte impregnation solution with a solid content of approximately 5 wt%. The viscosity at 25 °C was 85 mPa·s, and the water content was 85 ppm. Before use, the solution was filtered through a 0.45 μm filter membrane and degassed under vacuum for 15 min.
[0036] Step S5: Vacuum-atmospheric pressure cyclic impregnation and step-by-step desolventizing and drying The porous inorganic framework membrane obtained in step S3 was cut into 20cm × 30cm pieces and placed in a vacuum impregnation tank. A vacuum of 50 Pa was maintained for 20 minutes. The polymer electrolyte impregnation solution obtained in step S4 was injected, and a vacuum-atmospheric pressure cycle impregnation was performed three times: vacuum stage: 50 Pa / 15 minutes; back pressure stage: Ar back pressure to atmospheric pressure / 10 minutes. After impregnation, the membrane was removed and allowed to stand in an Ar atmosphere glove box at 23°C for 17 minutes to remove the surface solvent. It was then transferred to a vacuum oven and dried at 40°C and 800 Pa for 3 hours. Finally, it was deeply dried at 53°C and 50 Pa for 5 hours to obtain the composite solid electrolyte. The polymer electrolyte filled 92% of the framework pores.
[0037] Step S6: Heat treatment and slow cooling The composite solid electrolyte obtained in step S5 was heat-treated at 65°C for 2 hours under an Ar atmosphere, and then slowly cooled to room temperature at a rate of 2°C / min to obtain a composite solid electrolyte for substation batteries.
[0038] Example 2 A method for preparing a composite solid electrolyte for substation batteries, specifically comprising: The difference between this embodiment and Embodiment 1 is that wet purification is used instead of dry annealing in step S1, and the ratio of inorganic electrolyte to auxiliary filler in step S3 is an intermediate value. The remaining steps are the same as in Embodiment 1.
[0039] Step S1: LLZTO surface cleaning pretreatment (wet cleaning) In an Ar atmosphere glove box with a dew point ≤ -40℃, LLZTO powder was placed in a 0.02M citric acid solution (solid-liquid ratio 1g:10mL) and stirred at 25℃ for 3 min. The powder was washed with degassed deionized water until the filtrate pH reached 7.0, then rinsed with 0.01M LiOH solution for 30 s. After rinsing, the powder was filtered and washed with deionized water until neutral. It was then dried at 100℃ and 800Pa vacuum for 5 h to obtain pretreated LLZTO powder with a moisture content ≤300ppm.
[0040] Step S3: Water-based freeze forming 60g of pretreated LLZTO powder obtained in step S1, 15g of modified boron nitride nanosheets obtained in step S2, and 0.6g of PVA forming aid (0.8wt% of the total inorganic solid mass) were mixed and added to 150mL of degassed deionized water (inorganic electrolyte:water = 1:2.0). The pH was adjusted to 10.8 with 0.1 mol / L LiOH solution, and the aqueous phase exposure time was controlled at 60min. The coating thickness was 1.2mm, the belt speed was 0.4m / min, the pre-freezing temperature was -40℃, and other freeze-drying conditions were the same as in Example 1. The skeleton porosity was 52%.
[0041] Steps S4-S6 are the same as in Example 1. The polymer electrolyte filling rate is 90%.
[0042] Example 3 A method for preparing a composite solid electrolyte for substation batteries, specifically comprising: The difference between this embodiment and Embodiment 1 is that the ratio of inorganic electrolyte to auxiliary filler in step S3 is the lower limit value, while the other steps are the same as in Embodiment 1.
[0043] Step S3: Water-based freeze forming 70g of the pretreated LLZTO powder obtained in step S1, 30g of the modified boron nitride nanosheets obtained in step S2, and 0.75g of CMC forming aid (0.75wt% of the total inorganic solid mass) were mixed and added to 175mL of degassed deionized water (inorganic electrolyte:water = 1:2.5). The pH was adjusted to 10.2 with 0.1 mol / L LiOH solution, and the aqueous phase exposure time was controlled at 55min. The coating thickness was 0.8mm, the belt speed was 0.25m / min, the pre-freezing temperature was -50℃, and other freeze-drying conditions were the same as in Example 1. The skeleton porosity was 38%.
[0044] Steps S4-S6 are the same as in Example 1. The polymer electrolyte filling rate is 93%.
[0045] Example 4 (LATP system) A method for preparing a composite solid electrolyte for substation batteries, specifically comprising: In this embodiment, LATP is used as an inorganic solid electrolyte, and step S1 is carried out by wet purification (acetic acid treatment) with pH controlled at 7.5.
[0046] Step S1: LATP surface purification pretreatment (wet purification) In a glove box with a dew point ≤ -40℃ and N2 atmosphere, LATP powder was placed in 0.02M acetic acid solution (solid-liquid ratio 1g:10mL) and stirred at 25℃ for 3 min. The solution was washed with degassed deionized water until the pH of the filtrate was 7.0, and then rinsed with 0.01M LiOH solution for 30 s. After rinsing, the solution was filtered and washed with deionized water until neutral. The filtrate was then dried at 100℃ and 800Pa vacuum for 5 h to obtain pretreated LATP powder.
[0047] Step S2: Surface modification of auxiliary filler is the same as step S2 in Example 1.
[0048] Step S3: Water-based freeze forming 60g of the pretreated LATP powder obtained in step S1, 15g of the modified boron nitride nanosheets obtained in step S2, and 0.6g of PVP forming aid (0.8wt% of the total inorganic solid mass) were mixed and added to 150mL of degassed deionized water (inorganic electrolyte:water = 1:2.0). The pH of the suspension was adjusted to 7.5 using an NH3·H2O / NH4Cl buffer system, and the aqueous phase exposure time was controlled to be 70min. The coating thickness was 1.0mm, the belt speed was 0.3m / min, the pre-freezing temperature was -45℃, and other freeze-drying conditions were the same as in Example 1. The skeleton porosity was 48%.
[0049] Steps S4-S6 are the same as in Example 1. The polymer electrolyte filling rate is 91%.
[0050] Example 5 (LLZTO and LATP mixed system) A method for preparing a composite solid electrolyte for substation batteries, specifically comprising: In this embodiment, a mixture of LLZTO and LATP (mass ratio 1:1) is used as the inorganic solid electrolyte, and the pH is controlled at 9.0.
[0051] Step S1: Surface cleaning and pretreatment of mixed oxides LLZTO was treated according to step S1 (dry annealing) of Example 1 and LATP was treated according to step S1 (wet purification) of Example 4. The two powders were then mixed evenly at a mass ratio of 1:1 to obtain a pretreated mixed oxide powder.
[0052] Step S2: Surface modification of auxiliary fillers Same as step S2 in Example 1.
[0053] Step S3: Water-based freeze forming 50g of the pretreated mixed oxide powder obtained in step S1, 12.5g of the modified boron nitride nanosheets obtained in step S2, and 0.5g of sodium alginate forming aid (0.8wt% of the total inorganic solid mass) were mixed and added to 125mL of degassed deionized water (inorganic electrolyte:water = 1:2.0). The pH of the suspension was adjusted to 9.0 with 1wt% NH3·H2O, and the aqueous phase exposure time was controlled to be 50min. The coating thickness was 1.0mm, the belt speed was 0.3m / min, the pre-freezing temperature was -45℃, and other freeze-drying conditions were the same as in Example 1. The skeleton porosity was 50%.
[0054] Steps S4-S6 are the same as in Example 1. The polymer electrolyte filling rate is 92%.
[0055] Comparative Example 1 (without surface cleaning pretreatment) The difference between this comparative example and Example 1 is that the surface cleaning pretreatment in step S1 is omitted, and the LLZTO powder used is commercially available raw powder (unannealed and unwashed). The remaining steps are exactly the same as in Example 1.
[0056] Comparative Example 2 (auxiliary filler without surface modification) The difference between this comparative example and Example 1 is that the surface activation and silanization modification in step S2 are omitted, and the boron nitride nanosheets are made directly from untreated commercial raw materials. The remaining steps are exactly the same as in Example 1.
[0057] Comparative Example 3 (without pH zoning control and aqueous phase exposure time control) The difference between this comparative example and Example 1 is that the pH of the suspension is not controlled in step S3 (pure water is used directly, pH is about 6.5-7.0), and the exposure time of the aqueous phase is not controlled (the time from the powder being added to the water to the completion of pre-freezing is extended to 240 min).
[0058] Comparative Example 4 (Atmospheric pressure impregnation instead of vacuum - atmospheric pressure cyclic impregnation) The difference between this comparative example and Example 1 is that in step S5, the vacuum-atmospheric pressure cyclic impregnation is changed to atmospheric pressure impregnation (the skeleton membrane is immersed in the impregnation solution and kept at atmospheric pressure for 3 hours).
[0059] Comparative Example 5 (One-step rapid drying) The difference between this comparative example and Example 1 is that step S5 uses a one-step rapid drying method (directly drying the impregnated membrane at 60°C and 50Pa for 12 hours without step-by-step solvent removal), while the remaining steps are exactly the same as in Example 1.
[0060] Performance testing: Ionic conductivity (4.28-7.55×10) -4 Scm -1 Ionic conductivity was tested using the AC impedance method. The composite solid electrolyte was cut into circular pieces with a diameter of 10-16 mm, and the sample thickness was controlled at 30-120 μm. The sample was clamped between two electron blocking electrodes of the same diameter, which were polished stainless steel electrodes. During assembly, a constant pressure of 0.05-0.30 MPa was applied to the sample to ensure full contact between the electrodes and the composite solid electrolyte. The sample was then placed in an electrochemical test chamber with temperature control for at least 2 hours to equilibrate. Testing was performed using an electrochemical workstation or impedance analyzer, with a test frequency range of 1 MHz-0.1 Hz, an AC perturbation voltage of 5-10 mV, and a DC bias voltage of 0 V. For samples with significant polarization at the low-frequency end, the minimum test frequency could be reduced to 10 MHz. After the test, the intersection of the high-frequency end and the real axis, or the equivalent intersection of the high-frequency semicircle and the real axis in the complex plane impedance spectrum, is taken as the bulk resistance Rb of the sample. When obvious grain resistance, grain boundary resistance, and electrode polarization regions appear in the impedance spectrum, an equivalent circuit is used to fit the impedance spectrum, and the sum of the bulk resistance and grain boundary resistance is taken as the total ion conduction resistance of the sample. The ion conductivity is calculated according to the following formula: σ=L / (Rb×A), where σ is the ion conductivity of the composite solid electrolyte, in S / cm; L is the sample thickness, in cm; Rb is the ion conduction resistance of the sample, in Ω; and A is the effective contact area between the electrode and the sample, in cm². 2 The ionic conductivity was measured at 25℃, and the temperature was kept constant for at least 30 minutes.
[0061] Interfacial impedance (25℃, Ω·cm²): The composite solid electrolyte membrane was cut into 16mm diameter discs, with lithium metal electrodes (15.5mm diameter, 0.5mm thickness) sandwiched on both sides, assembling into a Li|electrolyte|Li symmetric CR2032 button cell. Assembly was carried out in a glove box filled with Ar atmosphere, with water and oxygen content <0.1ppm. The assembled battery was kept at 25℃ for 2-4 hours to allow the interface to stabilize (or stabilization conditions were selected according to actual needs). AC impedance spectroscopy was performed using an electrochemical workstation, with a frequency range of 10mHz-1MHz, an amplitude of 10mV, and a test temperature of 25℃. The interfacial impedance value (diameter of the semicircle in the mid-frequency region) was read from the Nyquist plot of the AC impedance spectrum.
[0062] Table 1 Performance test of composite solid electrolyte used in substation batteries
[0063] From Table 1, Figure 1 and Figure 2 It can be seen that the composite solid electrolytes obtained in Examples 1-5 all achieved an ionic conductivity of 5.99 × 10⁻⁶ at 25°C. -4 -7.21×10 -4 S / cm, interfacial impedance is 35.2-44.5 Ω·cm 2 This invention demonstrates that through a synergistic process involving surface purification pretreatment, auxiliary filler surface modification, low-water exposure aqueous system freeze-forming, vacuum-atmospheric pressure cyclic impregnation, and step-by-step solvent removal and drying, a composite solid electrolyte exhibiting both high ionic conductivity and low interfacial impedance was obtained. Specifically, Example 1, using an LLZTO system and purified by dry annealing, achieved a maximum ionic conductivity of 7.21 × 10⁻⁶. -4 S / cm, with an interface impedance as low as 38.6 Ω·cm 2 Example 4 uses the LATP system, which has a slightly lower ionic conductivity but still reaches 5.99 × 10⁻⁶. -4 The S / cm indicates that the present invention has good adaptability to different inorganic solid electrolyte systems. In contrast, Comparative Example 1, due to the omission of surface purification pretreatment, resulted in a residual Li2CO3 / LiOH passivation layer on the surface, causing the ionic conductivity to drop to 3.16 × 10⁻⁶. -4 S / cm, interface impedance rises to 67.4 Ω·cm 2 Comparative Example 2, due to the lack of surface modification of the auxiliary filler, exhibited a high interfacial impedance of 74.6 Ω·cm due to the absence of chemical bonding at the inorganic-polymer interface. 2 In Comparative Example 3, due to the lack of pH zone control and the extended exposure time to the aqueous phase (240 min), severe hydrolysis of the oxides occurred, resulting in an ionic conductivity of only 3.47 × 10⁻⁶. -4 The interfacial impedance increases dramatically to 96.3 Ω·cm (S / cm).2 Comparative Examples 4 and 5, due to insufficient filling rate during atmospheric pressure impregnation and solvent residue caused by one-step rapid drying, respectively, exhibited interfacial impedances of 89.5 Ω·cm. 2 and 91.8 Ω·cm 2 The results are significantly inferior to those of the embodiments. The above comparison shows that there is a close synergistic relationship between the various process steps of the present invention, and none of them can be omitted, which together ensures the excellent ion transport performance and interface stability of the composite solid electrolyte.
[0064] Although embodiments of this application have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of this application, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A composite solid electrolyte for substation batteries, comprising a porous inorganic framework and a polymer electrolyte filling the pores of the porous inorganic framework, characterized in that: The porous inorganic framework is composed of an inorganic solid electrolyte and a surface-modified electronic insulating auxiliary filler. The inorganic solid electrolyte in the porous inorganic framework has a mass percentage of 70-95 wt%. The inorganic solid electrolyte is LLZTO and / or LATP. The electronic insulating auxiliary filler is an electronic insulating material with a one-dimensional or two-dimensional morphology. The porous inorganic framework has a three-dimensional continuous porous structure formed by freeze drying. The porous inorganic framework has a porosity of 30-60% and a thickness of 30-120 μm before being filled with the polymer electrolyte. The polymer electrolyte comprises a lithium salt and a polymer matrix, wherein the lithium salt is LiTFSI and / or LiFSI, and the polymer matrix is PEO and / or PVDF-HFP; In the composite solid electrolyte, the porous inorganic framework has a mass percentage of 40-80 wt%, and the remainder is a polymer electrolyte.
2. The composite solid electrolyte for substation batteries according to claim 1, characterized in that, The electronic insulating auxiliary filler is selected from one or more of boron nitride nanosheets, alumina nanofibers, silica nanofibers, boehmite nanosheets, and aluminum nitride nanosheets; the surface-modified electronic insulating auxiliary filler is an auxiliary filler that has undergone surface activation and silanization modification.
3. The composite solid electrolyte for substation batteries according to claim 1, characterized in that, In the polymer electrolyte, the polymer matrix is a blend of PEO and PVDF-HFP, wherein the EO / Li molar ratio is 8-20:1, and the polymer electrolyte fills at least 85% of the pores of the porous inorganic framework.
4. A method for preparing a composite solid electrolyte for a substation battery as described in any one of claims 1-3, characterized in that, Includes the following steps: S1: The inorganic solid electrolyte powder is subjected to surface purification pretreatment under an inert atmosphere to obtain pretreated inorganic solid electrolyte powder. S2: Modified auxiliary filler is obtained by surface activation and silanization modification of electronic insulating auxiliary filler; S3: The pretreated inorganic solid electrolyte powder obtained in step S1 and the modified auxiliary filler obtained in step S2 are dispersed in degassed deionized water to form a suspension under a dry atmosphere with a dew point ≤ -40℃. The suspension is coated and then pre-frozen and freeze-dried to obtain a porous inorganic tape. The porous inorganic tape is then subjected to multi-stage gradient rolling to obtain a porous inorganic skeleton membrane. S4: Dissolve the polymer matrix and lithium salt in an organic solvent to prepare a polymer electrolyte impregnation solution; S5: The porous inorganic framework membrane obtained in step S3 is vacuum impregnated with the polymer electrolyte impregnation solution obtained in step S4, and then dried by step-by-step solvent removal under an inert atmosphere to obtain a composite solid electrolyte. S6: The composite solid electrolyte obtained in step S5 is heat-treated in an inert atmosphere and cooled to obtain a composite solid electrolyte for substation batteries.
5. The method for preparing the composite solid electrolyte for substation batteries according to claim 4, characterized in that, The surface cleaning pretreatment mentioned in step S1 is either dry annealing or wet cleaning. The dry annealing includes annealing the inorganic solid electrolyte powder in a continuously flowing inert atmosphere at 550-750℃ and a dew point ≤-40℃ for 1-4 hours, and then cooling it to no higher than 80℃ in an inert atmosphere after annealing. The wet purification process includes: treating the inorganic solid electrolyte powder in a 0.005-0.05M citric acid and / or acetic acid solution at 20-30℃ for 1-5 minutes, washing it, rinsing it with a 0.005-0.02M LiOH solution for 10-60 seconds, filtering it under vacuum and washing it with deionized water until the filtrate is neutral, and then vacuum drying it at 80-120℃.
6. The method for preparing the composite solid electrolyte for substation batteries according to claim 4, characterized in that, The surface activation described in step S2 is performed using oxygen plasma treatment at a power of 100-500W and a pressure of 10-100Pa for 1-10 minutes. The silanization modification includes: dispersing the surface-activated electronic insulating auxiliary filler in an ethanol / water mixed solvent, adding one or more of KH550, KH560, and KH570 as silane coupling agents, and reacting at 40-70℃ for 1-4 hours.
7. The method for preparing the composite solid electrolyte for substation batteries according to claim 4, characterized in that, In step S3, the solid content of the suspension is 35-60 wt%, and the time from adding degassed deionized water to completing the pre-freezing molding does not exceed 120 min. When the inorganic solid electrolyte is LLZTO, the pH of the suspension is 10.0-11.5; when the inorganic solid electrolyte is LATP, the pH of the suspension is 7.0-8.5; when the inorganic solid electrolyte is a mixture of LLZTO and LATP, the pH of the suspension is 8.5-10.
0. The suspension also contains a forming aid, which is selected from one or more of PVP, PVA, CMC, sodium alginate, and PEO. The amount of the forming aid added is 0.2-1.5 wt% of the total mass of the pretreated inorganic solid electrolyte powder obtained in step S1 and the modified auxiliary filler obtained in step S2.
8. The method for preparing the composite solid electrolyte for substation batteries according to claim 4, characterized in that, In step S3, the coating thickness is 0.3-1.5 mm, the pre-freezing temperature is -60℃ to -30℃, and the belt speed is 0.1-0.5 m / min; the freeze drying is: drying once at -35℃ to -20℃ and 1-10 Pa for 6-14 h, and then drying a second time at 20-40℃ for 2-6 h. The pre-frozen strips are stacked in 2-3 layers on a freeze-drying tray, with a breathable isolation membrane between adjacent strips. From top to bottom, the pore size and / or porosity of the breathable isolation membrane increases layer by layer. The multi-stage gradient rolling process consists of 2-5 stages, with a single-stage reduction rate of ≤20%. The rollers are preheated at 40-70℃ for 5-20 minutes before rolling.
9. The method for preparing the composite solid electrolyte for substation batteries according to claim 4, characterized in that, In step S4, the solid content of the polymer electrolyte impregnation solution is 3-15wt%, the viscosity at 25℃ is 10-500mPa·s, and the moisture content is not higher than 200ppm; in step S5, the vacuum impregnation is a vacuum-atmospheric pressure cyclic impregnation, with 2-5 cycles; the step-by-step desolventizing includes three stages: surface desolventizing at 20-25℃ under atmospheric pressure and inert atmosphere for 15-20min, low-temperature vacuum drying at 35-45℃ and ≤1000Pa for 2-4h, and deep vacuum drying at 50-55℃ and ≤100Pa for 4-6h.
10. The method for preparing the composite solid electrolyte for substation batteries according to claim 4, characterized in that, The heat treatment temperature in step S6 is 50-80℃, the time is 1-4h, and after heat treatment, it is slowly cooled at a rate of 0.5-5℃ / min.
Citation Information
Patent Citations
Composite solid electrolyte and preparation method thereof
CN115189017A
